INVESTIGATING THE ASSESSMENT PROCESS OF AN EFL TEACHER IN ASSESSING STUDENTS IN VOCATIONAL SCHOOL - Yudi Lesmana; Pupung Purnawarman (ELTIN Journal, 2024)
Inconsistent evaluations may result from unreliable assessments, which in turn may result in unjust assessments of students' abilities. Marginalised groups, such as English language learners coming from diverse cultural contexts, may experience a disproportionate impact from this phenomenon. Inaccurate evaluations have the potential to perpetuate educational inequities, reinforce stereotypes, and restrict avenues for academic progress. Consequently, the purpose of this study is to describe how an English teacher evaluate English proficiency of their students. This study employs  descriptive qualitative method. The subject of this research was an English teacher with eleven years of experience at a vocational school located in Lembang. The data was gathered via semi-structured interviews. A number of processes are involved in the analysis of data, including collection, documentation, identification, and interpretation. The findings showed several strategies used by the teacher in developing assessment tools. First, learning objectives are used by the teacher in developing assessment tools. In addition, the data also revealead that there are three factors that need to be considered in developing assessment tools such as students ability, difficulty level and the effectiveness. Furthermore, feedback and and regular assessment should be provided.